Manifestation of National-Cultural Characteristics in the Etymology of English and Uzbek Phraseological Units - Egamberganova Farangiz Xushnud qizi (Scientific Trends, 2024)
The development of cognitive linguistics and the application of its concepts in etymological studies may shed light on some issues in this difficult area. This is because the study of the gradual development of the cognitive function of the word has shown that it sometimes reflects its etymology. For this, we think that it would be useless to consider this issue using the terminological apparatus and analysis procedures of cognitive linguistics.